Investigating the Feasibility of Behavioral Nudges to Reduce the Phenomenon of Escape from Responsibility in Public Sector - Seyed Kamal Vaezi; Mahboubeh Hosseini (مدیریت دولتی)
ObjectiveThe aim of this research is to investigate the potential of behavioral nudges to reduce the escape from responsibility in executive systems (public sector). The field of behavioral sciences offers a wide range of nudge interventions that can be implemented at both individual and organizational levels. Therefore, this article attempts to redefine the concept of escape from responsibility in executive systems considering the administrative environment. By statistically analyzing biases in this area, the paper refers to solutions based on the capabilities of nudge theory and the concept of choice architecture to provide access to a more desirable situation in the field of escape from responsibility in the public sector.MethodsThe present research is based on the interpretive paradigm and qualitative methodology and was conducted using thematic analysis. The statistical population consisted of experts in the fields of management, law, and high officials of public sectors who were selected by the snowball sampling method. Data were collected through semi-structured interviews with experts and continued until theoretical saturation was reached.ResultsThe studies conducted identified 19 cognitive biases that can lead to the escape from responsibility among managers and employees. These biases essentially pave the way for escape from responsibility by deviating decision-making from the right path. The nudges identified in this research, influenced by theoretical and field studies, were categorized into six groups, which have the potential to prevent and control behaviors leading to omission in employees. ConclusionFindings show that managers and employees are subject to cognitive errors and biases in their understanding of duties and responsibilities. The results of the study also demonstrate that the principles of behavioral nudges can be applied in various organizations and fields. However, it is important to note that the effectiveness of nudges can vary depending on the specific context, targeted behaviors, and selected organizations. In this regard, the evidence is effective in reducing the evasion of responsibility and promoting positive behavior in public offices. Escape from responsibility among managers is a significant threat to the effectiveness of the organization and prevents progress towards achieving strategic goals. By understanding the underlying psychological underpinnings of this issue and applying the principles of behavioral science, organizations can effectively reduce this issue and foster a culture of responsible management. By empowering managers and by being aware of cognitive biases, promoting collective accountability, and using nudges to change behavior, organizations can create a safer working environment in which managers are motivated and take an active part in fulfilling their responsibilities and duties. This study showed that, according to Iranian experts, the motivational nudges, responsive nudges, and ethically based nudges have a greater and more effective ability to influence the handling of escape from responsibility in public sectors.